Dalbavancin in Gram-positive periprosthetic joint infections. (9th June 2022) - Simon, Sebastian; Frank, Bernhard J H; Hartmann, Susana; Hinterhuber, Laetitia; Reitsamer, Michael; Aichmair, Alexander; Dominkus, Martin; Söderquist, Bo; Hofstaetter, Jochen G
Abstract: Objectives: The unique properties of dalbavancin (DAL) emphasize the need to explore its clinical benefits to treat periprosthetic joint infections (PJIs). The present study aimed to compare the treatment outcome of dalbavancin with Standard of Care (SoC) in hip and knee PJIs. Methods: Eighty-nine patients were selected for each group of this study based on our prospectively maintained PJI database. A 1:1 propensity score-matching was performed between patients who received at least two doses of dalbavancin and those who received SoC. Patients were matched based on demographics, joint, patient risk factors, Musculoskeletal Infection Society (MSIS) criteria, surgical management and type of infection. Treatment outcome was evaluated considering re-infection and re-revision rates, safety and tolerability of dalbavancin after a minimum of 1 year follow-up. Results: Infection eradication was achieved in 69 (77.5%) and 66 (74.2%) patients of the DAL and SoC groups, respectively. Thirteen (14.6%) patients in the DAL group and 12 (13.5%) patients in the SoC group had an infection-related re-revision. The most prevalent microorganisms among the two groups were Staphylococcus epidermidis (32.3%), Staphylococcus aureus (13.8%) and Cutibacterium spp. (11.3%). There were significantly less Gram-positive bacteria ( P = 0.03) detected in patients who received dalbavancin (17.4%) treatment compared with those treated with SoC (48.0%) in culture-positive re-revisions. Conclusions: Dalbavancin treatment for Gram-positive PJIs resulted in a similar outcome to SoC, with excellent safety and low rate of adverse effects. Dalbavancin seems to be a promising antimicrobial against PJIs by reducing the risk of Gram-positive re-infections and allowing a less frequent dosage with potential outpatient IV treatment.